The Representation of the Concept of Love in English Children and Adult Song Lyrics Based on Transitivity - Tia Liztiawati; Nurhayati Nurhayati (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2021)
The purpose of the study is to explain the way the concept of love is represented in adult's song and children's song, using the conceptual framework of transitivity. In this research, the writer used descriptive qualitative research. The data of the research are obtained from the internet. The lyrics are downloaded from the website and YouTube channel providing by Laci Abdul Jalil, lirik.kapanlagi.com, Kak Zepe, The Kiboomers, and bus song. The result of this study are as follows: 1) The three main processes; behavioral, relational, and material, are dominating the total number of occurrences in the selected adult songs. The behavioral process is the highest for 24,83% with a total of 435 occurrences. The relational process comes second for 22,53%. The smallest percentage for the main process is the material process for 19,54%. On the other hand, the three main processes; mental, material, and relational, are dominating the total number of occurrences in the selected children's songs. 2) The most dominant participants found in both songs are senser. That is consciously being who feels, thinks, sees, or perceives (love). 3) The circumstances of the time in both songs show that the adult songs are more varied than children's songs.